Meaning and experiences in managing primary education development programme school funds among public primary school headteachers in Tanzania - Mwinjuma, Juma Saidi (2016)
The main purpose of the study was to understand the meaning and experiences of primary schools head teachers in managing Primary Education Development Programme (PEDP) funds. The study was guided by two major research questions. The first question is; what meaning do head teachers construe regarding the management of Primary Education Development Programme (PEDP) funds? And the second is; how do head teachers manage Primary Education Development Programme funds? The study used the descriptive phenomenological as it was deemed relevant to examine head teachers‘ meaning and experiences about the phenomenon. Data was collected using semi-structured interviews with head teachers, observations and analysis of documents at public primary schools. Seven informants were selected from a number of schools based on educational attainment and experience serving as a head teacher. Interviews were recorded, transcribed verbatim and analyzed systematically. In addition, data from observations and documents analysis supported the data obtained from in-depth interviews. Four major themes that emerged from analysis of data are: allocation of funds, accountability, control of funds and competence and traits. The study revealed bureaucracy, insufficiency and inconsistency of funding and delays of disbursements as sub themes associated with allocation of funds. Accountability, as a theme in this study is associated with head teachers considering themselves responsible, challenging roles, adhering to ethics, and complying with instructions. It was also revealed in this study that, limited resources, selection of options, accepting duties and participatory decisions are sub themes associated with control of funds. Furthermore, the study revealed that personal aspiration, level of education, democratic leadership support from others and mindfulness of school funds as sub themes linked to competence and traits. Four major conclusions were drawn from this study. First, direct school funding has only offered limited solutions to resources acquisition in schools due to availability of insufficient funds in schools. Secondly, schools do not have full autonomy to use the allocated funds to fulfil locally determined school requirements. Thirdly, at school levels there is a state of confusion between participatory decision making and the issue of taking responsibilities. Fourthly, there is a need and urgency to build their capacities through continuous trainings. Based on these conclusions, the study recommends for systemic approach to understanding allocation of PEDP funds in order to improve quality of education in public primary schools in Tanzania. Finally, for head teachers and other stakeholders to act and facilitate effective implementation of educational programmes such as PEDP, there is a need and urgency to build their capacities to competently manage these educational programmes.